Evaluation of the depth of the gingival surco after the use of the retractor 00 thread for class V restorations in patients attended at the dental clinic of the university of The Americas - Giacometti Velasco, Sebastián (2018)
Objective: To evaluate the depth of the gingival sulcus after the use of retractor thread 00 for class V restorations. Materials and Methods: For the present investigation, 84 dental pieces were evaluated in 46 patients, both men and women who attended the Clinic of the University of the Americas. Probing and control were performed at 72 hours to determine if it affected the retractor thread at the level of the gingival sulcus. Results: 64.29% of the pieces evaluated showed a change, while 35.71% remained in the normal standard. Regarding the differentiation of gingival biotypes, a greater change in the measurement of the gingival sulcus was obtained in patients with a thin biotype with 64.81% of the pieces evaluated in relation to the gross biotype with 35.19%. In the present study, the existence of bleeding at the level of the gingival sulcus was also determined at the time of the drilling: initial, middle and final. With bleeding results of 7.69%, 34.62% and 57.69% respectively. Conclusion: It was determined that there are significant differences with respect to the depth of the furrow presented in the initial, middle and final drilli ng, however the level of depth of the furrow was higher in the Middle Probe. This confirms that the use of the retractor thread a ffects the periodontium when performing the restorative procedure. In this study it was shown that 64.29% of the pieces evaluated were affected.